Epinecidin-1, an Antimicrobial Peptide Derived From Grouper (Epinephelus coioides): Pharmacological Activities and Applications - Chee, Pui Ying; Mang, Morokot; Lau, Ern Sher; Tan, Loh Teng-Hern; He, Ya-Wen; Lee, Wai-Leng; Pusparajah, Priyia; Chan, Kok-Gan; Lee, Learn-Han; Goh, Bey-Hing (Frontiers in Microbiology, 2019)
Epinecidin-1 is an antimicrobial peptide derived from the orange-spotted grouper (Epinephelus coioides). The mature epinecidin-1 peptide is predicted to have an amphipathic -helical structure and a non-helical hydrophilic domain at the C-terminal RRRH. The majority of work studying the potential pharmacological activities of epinecidin-1, utilize synthesized epinecidin-1 (Epi-1), which is made up of 21 amino acids, from the amino acid sequence of 22-42 residues of Epi-1 – GFIFHIIKGLFHAGKMIHGLV. The synthetized Epi-1 peptide has been demonstrated to possess diverse pharmacological activities, including antimicrobial, immunomodulatory, anticancer, and wound healing properties. It has also been utilized in different clinical and agricultural fields, including topical applications in wound healing therapy as well as the enhancement of fish immunity in aquaculture. Hence, the present work aims to consolidate the current knowledge and findings on the characteristics and pharmacological properties of epinecidin-1 and its potential applications.